2019
DOI: 10.7759/cureus.4883
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Supraventricular Tachycardia

Abstract: Supraventricular tachycardia is a common emergency department (ED) pathology that frequently leads to hospital admission, but this may not be necessary in all cases. Here, we present a supraventricular tachycardia patient who was discharged from the ED after vagal maneuvers. This case demonstrates evidence that judicious emergency physicians can discharge supraventricular tachycardia patients home safely and gives impetus for a data-driven protocol for discharging these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…These people need urgent cardioversion if their heartbeat is not in sinus rhythm. If it is found that they are in acceptable sinus tachycardia, the underlying cause must be addressed [4]. Here, we present the case of a patient with unstable PSVT who refused electrical cardioversion at a resource-limited rural hospital in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…These people need urgent cardioversion if their heartbeat is not in sinus rhythm. If it is found that they are in acceptable sinus tachycardia, the underlying cause must be addressed [4]. Here, we present the case of a patient with unstable PSVT who refused electrical cardioversion at a resource-limited rural hospital in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%